Personality of Female Athletes in Sports Talent Senior High School (SMANKO) Bengkulu - Ari Sutisyana; Yahya Eko Nopiyanto; Tono Sugihartono; Yarmani Yarmani; Syafrial Syafrial; Puput Eka Novianti (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This research aimed to determine the personality of female athletes in Sport Talent Senior High School (SMANKO) Bengkulu Province. This research used a qualitative descriptive method. The subjects of this study were all female athletes in the Sports Talent Senior High School (SMANKO) Bengkulu Province, totaling 38 athletes. The instruments and data collection techniques used in this research were observation, interviews, questionnaires, and documentation. The data analysis technique used was a descriptive analysis with a percentage. The results of the study stated that the observation percentage was 60.53%, the general questionnaire was 57.90%, the interview was 55.26%, and the documentation was 42.10%. Based on the results of the study, it can be concluded that the personality of female athletes in the  sports talent senior high school (SMANKO) Bengkulu was classified as good.